COVID-19 respiratory support outside the ICU's doors. An observational study for a new operative strategy - Bignami , Elena; Bellini, Valentina; Maspero, Giada; Pifferi, Barbara; Fortunati Rossi, Leonardo; Ticinesi, Andrea; Craca, Michelangelo; Meschi, Tiziana; Baciarello, Marco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: During the first wave of the Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) pandemic, we faced a massive clinical and organizational challenge having to manage critically ill patients outside the Intensive Care Unit (ICU). This was due to the significant imbalance between ICU bed availability and the number of patients presenting Acute Hypoxemic Respiratory Failure caused by SARS-CoV-2-related interstitial pneumonia. We therefore needed to perform Non-Invasive Ventilation (NIV) in non-intensive wards to assist these patients and relieve pressure on the ICUs and subsequently implemented a new organizational and clinical model. This study was aimed at evaluating its effectiveness and feasibility.Methods: We recorded the anamnestic, clinical and biochemical data of patients undergoing non-invasive mechanical ventilation while hospitalized in non-intensive CoronaVirus Disease 19 (COVID-19) wards. Data were registered on admission, during anesthesiologist counseling, and when NIV was started and suspended. We retrospectively registered the available results from routine arterial blood gas and laboratory analyses for each time point.Results: We retrospectively enrolled 231 patients. Based on our criteria, we identified 46 patients as NIV responders, representing 19.9% ​​of the general study population and 29.3% of the patients that spent their entire hospital stay in non-ICU wards. Overall mortality was 56.2%, with no significant differences between patients in non-intensive wards (57.3%) and those later admitted to the ICU (54%)Conclusions: NIV is safe and manageable in an emergency situation and could become part of an integrated clinical and organizational model.